Analisis Efektivitas Kebijakan Penyaluran Beasiswa KIPK Aspirasi di Indonesia - Rohmatul Jannah; Dida Oktavian; Aldi Rizal Syahputra (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Education is a constitutional right of citizens that must be fulfilled by the state, as mandated in Article 31 of the 1945 Constitution of the Republic of Indonesia. One of the policy instruments used by the government to ensure equitable access to higher education is the Indonesia Smart Card for Higher Education (Kartu Indonesia Pintar Kuliah/KIP-K) Program, including the KIP-K Aspirasi scheme, which is distributed through recommendations from members of the House of Representatives (DPR). Although normatively KIP-K Aspirasi aims to expand access to higher education for students from underprivileged families, its implementation across various universities indicates a gap between policy objectives and practices in the field.This study aims to analyze the effectiveness of the KIP-K Aspirasi scholarship distribution policy in Indonesia and to identify supporting factors, inhibiting factors, and policy improvement efforts from the perspective of public policy law. The research method employed is a descriptive qualitative approach based on a literature review, with data sources consisting of laws and regulations, policy documents, and relevant previous research findings. The analysis uses the theoretical framework of public policy implementation and policy effectiveness indicators.The results show that the effectiveness of KIP-K Aspirasi still faces several obstacles, particularly in terms of transparency, targeting accuracy, and the smooth disbursement of funds. In addition, the absence of specific legal regulations governing the KIP-K Aspirasi mechanism raises issues of legal certainty, accountability, and the potential politicization of the policy. Therefore, this study recommends strengthening regulations, increasing transparency, and reinforcing oversight systems so that the KIP-K Aspirasi policy can be implemented more effectively and equitably as an instrument for fulfilling the right to higher education.